Morphological Characteristics and Potential of Sago (Metroxylon spp.) in Lingga Regency, Riau Islands, Indonesia - Primadhika Al Manar; Ervizal Amir Muhammad Zuhud; Nuri Andarwulan; Mochamad Hasjim Bintoro (Institut Pertanian Bogor (IPB University), 2023)
Sago (Metroxylon) is one of the local food species with development potential. Lingga Regency is one of the potential locations for sago development. However, no research on the morphological characteristics and production of sago in Lingga Regency has been conducted. The purpose of this research is to determine the morphological characteristics and production of sago in Lingga Regency. This study's sago plants came from six sago-producing villages. Before and after the sago trees were harvested, morphological characteristics and production were observed, with random sampling at each research site. Field observations on the potential of sago stands were conducted at the study site using the transect method with a single plot. Based on morphological characters there are two types of sago in Lingga: spiny and thornless sago. The morphological characteristics and sago production vary greatly between research sites. Sago stands have a production potential ranging from 3.37 to 14.55 tons ha-1. Because they have a starch content of more than 200 kg stem-1, the majority of sago accessions in Lingga are superior accessions with the potential to be further developed. Superior sago comes from the villages of Musai, Pekaka, Keton, and Teluk.